Extracorporeal Photopheresis in Children with Chronic Graft-Versus-Host Disease - Andrey Kozlov; Maria Estrina; Olesia Paina; Tatiana Bykova; Anna Osipova; Polina Kozhokar; Zhemal Rakhmanova; Irina Solodova; Elena Morozova; Alexander Alyansky; Irina Kulagina; Asmik Gevorgian; et al. (MDPI AG, 2021)
Chronic graft versus host disease (cGVHD) remains a major complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT). It significantly decreases survival and quality of life. The present study demonstrates retrospective data on extracorporeal photopheresis (ECP) in children with cGVHD. A total of 42 children with steroid-refractory cGVHD were enrolled in the study. The majority of patients had acute leukemia (n = 32, 76%). All patients received ECP as second (n = 18, 43%) or third (n = 24, 57%) line of therapy. Initial ECP schedule consisted of bimonthly regimen for two consecutive days with possibility of further tapering according to response. Any concurrent treatment administered before ECP could be continued if considered necessary. Complete response to ECP was registered in seven (17%) patients and partial response in 24 (57%). Overall response according to organ involvement was as follows: skin (n = 24, 75%), mucous membranes (n = 16, 73%), liver (n = 8, 80%), gut (n = 4, 80%), lungs (n = 2, 22%) and joints (n = 2, 67%). Five-year overall, progression-free and failure-free survival was 57%, 56% and 30%, respectively. Non-relapse mortality at 5 years was 14%. We didn't observe any clinically significant complications in children that could be attributed to the procedure. ECP remains important and safe treatment option in children with cGVHD.